ANALISIS KONSENTRASI TERHADAP KEMAMPUAN SHOOTING ATLET FUTSAL IKOR FIKK UNM - Darul Husnul; Iyan Nurdiyan Haris (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2023)
This decrease in concentration is marked by athletes exhibiting behavior that is detrimental to appearance. Athletes can disrupt their concentration when athletes are unable to pay attention to relevant stimuli and ignore irrelevant stimuli. When doing competition activities or sports activities, the stimulus always comes together. This requires athletes to always focus on the activity being carried out. Stimuli can be in the form of instructions from the coach, movements of opponents, teammates, noise from the audience and behavior of opposing supporters. Shooting is one of the basic futsal techniques that every player needs to master. Shooting is an attempt to kick the ball with the aim of putting the ball into the goal using accuracy and concentration so that the ball is directed according to the desired goal. shooting is a ball kick that is very hard and accurate and is carried out by a player towards the goal. In the futsal game, From the data above, the value of R = 0.991 is obtained, which means a concentration of 99.1% on the shooting results. with a value of Sig = 0.00. sig value <0.05 it can be said that the data is significant. This result also concludes that the better the concentration results of the players, the better the shooting results will be, this is because the other players are very focused on running the match even though they are very tired.